Principles and Practice of Anesthesia for Thoracic Surgery - Slinger, MD, FRCPC, Peter (Springer New York : Imprint: Springer, 2011)
Comprehensive, authoritative, and up-to-date, Principles and Practice of Anesthesia for Thoracic Surgery covers all aspects of anesthesia for diagnostic and therapeutic thoracic procedures, including advances not addressed by other volumes, such as extracorporeal ventilatory support, new chest imaging modalities, lung isolation with a difficult airway, pulmonary thromboendarterectomy, chronic postthoracotomy pain, management of one-lung anesthesia, lung isolation, lung transplantation,and pharmacologic therapy of pulmonary hypertension. The book is aimed at residents, fellows, and staff anesthesiologists, as well as nurse anesthetists, nurse practitioners, and anesthesia assistants. Major topics and special features: Underlying basic science Preoperative evaluation of the patient Airway procedures Mediastinal procedures The complicating factors of significant co-morbidities and/or advanced age Uncommon and complex thoracic surgical procedures  Post-operative care End-stage lung disease Pediatric Thoracic Anesthesia "Key Points" summarizing each chapter's Highlights Clinical case discussion, with the Author's recommendations, in every clinical chapter.